Improved thermal/chemical stability of flexible Ag NWs/Chitosan composite electrode integrated by chemical welding and sequential protection for better PV performance. (23rd July 2021) - Liu, Jingling; Guo, Longfei; Liu, Zhiwen; Shen, Qihang; Gao, Xueru; Zhang, Ziqi; Liu, Xinsheng; Cheng, Ke; Du, Zuliang
Abstract: An integration strategy of chemical welding and subsequent protection was demonstrated to address silver nanowires (Ag NWs)-based issues. Preferentially, a halogenated salt of NaCl solution was used to stimulate the junction welding thus to reduce the junction resistance, by virtue of the autocatalytic redox of Ag atoms with halogen ions and dissolved oxygen molecules. Subsequently, chitosan, possessing the biocompatible, degradable, environmentally friendly non-toxic features, was embedded to protect Ag NWs. With these two steps, the composite electrode consisting Ag NWs and chitosan reaches a lowest sheet resistance of ∼8 Ω, with a transmittance over 80% at 550 nm, along with high thermal and chemical stabilities, accompanying with excellent flexibility. Besides, it also prompts a synergistic improvement when pioneered in Cu(In, Ga)Se2 (CIGS) device as a transparent conductive electrode. It yields a power conversion efficiency of 6.6%, with 32% improvement relative to that bare Ag NWs, and 85% of the conventional one. Our findings present a new strategy for addressing instable/inefficient Ag NWs-based devices, driving their rapid development and its practical applications.